Ischaemic stroke in young adults: A comparative study between Malaysia and Australia - Tan, K.S.; Tan, C.T.; Churilov, L.; Mackay, M.; Donnan, G.A. (2010)
Background and Objectives: There is a paucity of comparative studies on young strokes between populations of different ethnicities and geographical regions. The purpose of this study was to compare the patterns, risk factors and etiologies of ischaemic stroke in younger patients between stroke registries in Malaysia and Australia. Methods: From January 2007 to March 2008, all consecutive ischaemic stroke patients from the age of 18 to 49 were studied. Results: There were 67 patients for Malaysia and 61 for Australia, with 4 deaths in the Malaysian series (case-fatality of 6%), and no deaths for Australia. The mean age was 41.5 +/- 8.8 yrs for Malaysia and 40.1 +/- 8.8 years for Australia. The ethnic origin was Malays, Chinese and Indian for Malaysia, and Caucasians (85%) for Australia. The sex ratio was M : F = 1.4 : 1 for Malaysia and 1.54 : 1 for Australia. The differences in risk factors for Malaysia versus Australia were: Diabetes (OR 7.25; 95% CI 2.78-19.45), hypertension (OR 6.42; 95% CI 2.75-15.22) and chronic renal disease (OR 5.2; 95% CI 1.02-35.87). Conversely, smoking was a significant risk factor for Australia (OR 2.75; 95% CI 1.2-6.37). The Malaysian patients have significantly higher proportions of large vessel atherosclerosis and small vessel occlusion by TOAST classification, accounting for 60% of patients, while the Australian series had greater proportions of cardioembolism and patients in the determined aetiologies category, specifically vascular dissection. Conclusion: There were significantly more large vessel atherosclerosis and small vessel occlusion among young Malaysians with ischaemic stroke as compared to Australia.